Securitization and Market Power – Evidence from European Banks - Herwald, Sarah; Uhde, André
Employing a unique hand-collected sample of 881 securitization transactions issued by 59 stock-listed banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically investigates if and how market power in the loan and deposit market may influence European banks’ incentives to engage in securitization activities. We construct product-specific residual Lerner Indices to measure market power in the loan and deposit market separately. Our results suggest that banks with higher loan and deposit market power securitize less, consistent with a reduced need for risk transfer and a reduced reliance on market-based funding. Various sensitivity analyses further show that these relationships vary across underlyings, issuance frequencies, and different time stages of securitization in Europe. Our findings contribute to the literature by disentangling loan and deposit market power as two further distinct determinants of securitization and thus, offer important insights regarding the ongoing policy debates on the consolidation of European banking markets and the revitalisation of the European securitization market.
Keywords: Securitization; market power; European banking

The impact of market power on banks' ESG scores - evidence from Europe and North America - Voigt, Simone; Uhde, André
This paper empirically examines the relationship between market power and Environmental, Social, and Governance (ESG) scores of banks in Europe and North America from 2010 to 2021, focusing separately on loan and deposit markets. Employing the Lerner Index as a non-structural measure of market power, our findings suggest that the impact of banking market power on ESG scores varies by region and the respective loan or deposit market. We find a negative effect of loan and deposit market power on ESG scores of European banks whereas the opposite effect can be observed for North American banks exhibiting loan market power. Further sensitivity analyses reveal that factors such as banks being Global Systemically Important (G-SIBs), and different ESG-related events like the Paris Agreement, the reemergence of the #MeToo movement and the COVID-19 pandemic may also explain the relationship between bank market power and ESG scores. Overall, our results underline that banking market power plays a pivotal role in enforcing ESG commitments in banking, offering key insights for policymakers, regulators, and banking stakeholders.
Keywords: Market Power; ESG scores; European and North American banking markets

The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André (Journal of Risk Finance)
Purpose Academic research has intensively analyzed the relationship between market concentration or market power and banking stability but provides ambiguous results, which are summarized under the concentration-stability/fragility view. We provide empirical evidence that the mixed results are due to the difficulty of identifying reliable variables to measure concentration and market power. Design/methodology/approach Using data from 3,943 banks operating in the European Union (EU)-15 between 2013 and 2020, we employ linear regression models on panel data. Banking market concentration is measured by the Herfindahl–Hirschman Index (HHI), and market power is estimated by the product-specific Lerner Indices for the loan and deposit market, respectively. Findings Our analysis reveals a significantly stability-decreasing impact of market concentration (HHI) and a significantly stability-increasing effect of market power (Lerner Indices). In addition, we provide evidence for a weak (or even absent) empirical relationship between the (non)structural measures, challenging the validity of the structure-conduct-performance (SCP) paradigm. Our baseline findings remain robust, especially when controlling for a likely reverse causality. Originality/value Our results suggest that the HHI may reflect other factors beyond market power that influence banking stability. Thus, banking supervisors and competition authorities should investigate market concentration and market power simultaneously while considering their joint impact on banking stability.
Keywords: market concentration; market power; banking stability; European banking

Risk allocation through securitization – Evidence from non-performing loans - Wengerek, Sascha Tobias; Hippert, Benjamin; Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique and hand-collected sample of 648 true sale loan securitization transactions issued by 57 stock-listed banks across the EU-12 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the relationship between true sale loan securitization and the issuing banks’ non-performing loans to total assets ratios. Overall, we provide evidence for a negative impact of securitization on NPL exposures suggesting that banks predominantly used securitization as an instrument of credit risk transfer and diversification. In addition, the analysis at hand reveals a time-sensitive relationship between securitization and NPL exposures. While we observe an even stronger NPL-reducing effect through securitization during the non-crisis periods, the effect reverses during and after the global financial crisis suggesting that banks were forced to provide credit enhancement and employ securitization as a funding management tool. Along with the results from a variety of sensitivity analyses our study provides important implications for the recent debate on reducing NPL exposures of European banks by revitalizing the European securitization market.
Keywords: European Banking; Non-performing Loans; Securitization

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric GARCH models with long memory are in- troduced. The estimation of the nonparametric scale function is carried out by an adapted version of the SEMIFAR algorithm (Beran et al., 2002). Recurring on the revised recommendations by the Basel Committee to measure market risk in the banks' trading books (Basel Committee on Banking Supervision, 2013), the semi- parametric GARCH models are applied to obtain rolling one-step ahead forecasts for the Value at Risk (VaR) and Expected Shortfall (ES) for market risk assets. In addition, standard regulatory traffic light tests (Basel Committee on Banking Supervision, 1996) and a newly introduced traffic light test for the ES are carried out for all models. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long memory GARCH models are an attractive alternative to their conventional, parametric counterparts.
Keywords: Semiparametric; long memory; GARCH models; forecasting; Value at Risk; Expected Shortfall; traffic light test; Basel Committee on Banking Supervision

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; Credit risk transfer; Effective tax rates; European banking

Determinants of CDS Trading on Major Banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
This paper empirically investigates determinants of the outstanding net notional amount of credit default swaps (CDSs) contracts written on banks. We extend and complement the previous literature dealing with CDS trading by analyzing a comprehensive set of CDS tradingspecific, bank-fundamental, macroeconomic and bank-institutional determinants. We find that risk hedging clearly dominates an investor’s speculation and arbitrage motive, while the latter, however, exhibits the strongest impact on the outstanding net notional amount of bank CDSs. Furthermore, being classified as a G-SIB, being a constituent of the main CDS index and the equity trading volume may significantly explain changes in the outstanding CDS net notional on banks. The analysis at hand provides important implications for both academics and practitioners, since understanding the trading motives of bank CDS investors provides a deeper insight into the opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Risk allocation through securitization - Evidence from non-performing loans - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
Employing a unique and hand-collected dataset of securitization transactions by European banks, this paper analyzes the relationship between true sale loan securitization and the issuing banks’ non-performing loans to total assets ratios (NPLRs). We provide evidence for an NPLR-reducing effect during the boom phase of securitizations suggesting that banks (partly) securitized NPLs as the most risky junior tranche. In contrast, we find the reverse effect during the crises period indicating that issuing banks demonstrated `skin in the game'. A variety of sensitivity analyses provides further important implications for the vital debate on reducing NPL exposures and regulating securitization markets.
Keywords: European Banking; Non-performing Loans; Risk Allocation; Securitization

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; Credit risk transfer; Effective tax rates; European banking

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; credit risk transfer; effective tax rates; European banking

Determinants of CDS trading on major banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
Employing credit default swap (CDS) data for a sample of 52 major banks across 18 countries from 2008 to 2016, this paper investigates determinants of the outstanding net notional amount of CDS which are written on banks. We extend the current literature dealing with CDS trading by analyzing further CDS trading-specific, fundamental bank-specific as well as macroeconomic and institutional determinants with a focus on bank CDS trading. We find that, next to well-discussed determinants for corporate firms in the literature, especially a bank's tail risk, capital adequacy, loan portfolio and business model affect a bank's outstanding CDS net notional. This finding indicates that investors in the bank CDS market partly have a recourse to a fundamental analysis for their investment decision. Our study fills an important gap since empirical studies have solely focused on sovereign and corporate CDS yet. In addition, the analysis at hand provides important implications for both academics and practitioners since understanding the trading motives of bank CDS investors gives deeper insights into the still opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Determinants of CDS trading on major banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
Employing credit default swap (CDS) data for a sample of 52 major banks across 18 countries from 2008 to 2016, this paper investigates determinants of the outstanding net notional amount of CDS which are written on banks. We extend the current literature dealing with CDS trading by analyzing further CDS trading-specific, fundamental bank-specific as well as macroeconomic and institutional determinants with a focus on bank CDS trading. We find that, next to well-discussed determinants for corporate firms in the literature, especially a bank's tail risk, capital adequacy, loan portfolio and business model affect a bank's outstanding CDS net notional. This finding indicates that investors in the bank CDS market partly have a recourse to a fundamental analysis for their investment decision. Our study fills an important gap since empirical studies have solely focused on sovereign and corporate CDS yet. In addition, the analysis at hand provides important implications for both academics and practitioners since understanding the trading motives of bank CDS investors gives deeper insights into the still opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Determinants of CDS trading on major banks - Hippert, Benjamin; Uhde, André
Employing credit default swap (CDS) data for a sample of 52 major banks across 18 countries from 2008 to 2016, this paper investigates determinants of the outstanding net notional amount of CDS which are written on banks. We extend the current literature dealing with CDS trading by analyzing further CDS trading-specifi c, fundamental bank-speci fic as well as macroeconomic and institutional determinants with a focus on bank CDS trading. We fi nd that, next to well-discussed determinants for corporate firms in the literature, especially a bank's tail risk, capital adequacy, loan portfolio and business model affect a bank's outstanding CDS net notional. This finding indicates that investors in the bank CDS market partly have a recourse to a fundamental analysis for their investment decision. Our study fills an important gap since empirical studies have solely focused on sovereign and corporate CDS yet. In addition, the analysis at hand provides important implications for both academics and practitioners since understanding the trading motives of bank CDS investors gives deeper insights into the still opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

The relationship between credit risk transfer and non-performing loans. Evidence from European banks - Uhde, André; Wengerek, Sascha Tobias
Employing a unique and hand-collected sample of 648 true sale loan securitization transactions issued by 57 stock-listed banks across the EU-12 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the relationship between true sale loan securitization and the issuing banks' non-performing loan to total assets ratios (NPLRs). We provide evidence for an NPLR-reducing effect during the boom phase of securitizations in Europe suggesting that banks in our sample may (partly) securitize NPLs as the most risky junior tranche and do not (fully) retain NPLs as a reputation and quality signal towards less informed investors in imperfect capital markets. In contrast, we fi nd the reverse effect during the crises period in Europe indicating that issuing banks provided credit enhancement and demonstrated `skin in the game'. Our baseline result remains robust when controlling for endogeneity concerns and a potential persistence in the time series of the NPL data. Moreover, results from a variety of sensitivity analysis reveal that the NPLR-reducing effect is stronger for opaque securitization transactions, for issuing banks exhibiting higher average levels of NPLRs and for banks operating from non-PIIGS countries. In addition, a reduction of NPLRs through securitization is observed for issued collateralized debt obligations, residential mortgage-backed securities, consumer and other unspeci ed loans as well as for non-frequently issuing, systemically less important and worse-rated banks. Our analysis offers essential insights into the loan risk allocation process through securitization and provides important implications for the vital debate on reducing NPL exposures and the process of revitalizing and regulating the European securitization market.
Keywords: European Banking; Non-performing Loans; Risk Allocation; Securitization

Risk-taking incentives through excess variable compensation: Evidence from European banks - Uhde, André (The Quarterly Review of Economics and Finance)
Employing compensation data provided by 63 banks from 16 European countries for the period from 2000 to 2010 this paper empirically investigates the impact of excess variable compensation on bank risk. As a main finding, we provide evidence for a risk-increasing impact of excess variable pay for both executive variable cash-based and variable equity-based compensation. This baseline finding holds under various robustness checks, in particular when controlling for likely reverse causality between bank risk and variable compensation by employing Granger-causality tests and instrumental variable regressions. In addition, results from a large number of sensitivity analyses including board and banking characteristics as well as the financial crisis period and the quality of a country's regulatory framework provide further important implications for banking regulators and politicians in Europe.
Keywords: Banking; Executive compensation; Risk-taking; Financial stability

Determinants of loan securitization in European banking - Farruggio, Christian; Uhde, André (Journal of Banking and Finance)
Analyzing 75 securitizing and non-securitizing stock-listed banks in the EU-13 plus Switzerland over the period from 1997 to 2010, this paper provides empirical evidence that loan securitization in Europe is a composite decision based on bank-specific as well as market- and country-specific determinants. In addition, we find that these determinants remarkably change when separately investigating securitization transactions during the pre-crisis and crisis period. Moreover, results from several subsample regressions reveal that determinants of loan securitizations in Europe depend on the transaction type, the underlying asset portfolio and the regulatory and institutional environment under which banks operate.
Keywords: Securitization; Determinants; European banking

Credit risk securitization and bank soundness: Evidence from the microlevel for Europe - Michalak, Tobias C.; Uhde, André (Quarterly Review of Economics and Finance)
Using a unique sample of 749 cash and synthetic securitization transactions issued by 60 stock-listed bank holdings in the EU-13 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a negative impact on the issuing banks’ financial soundness. Baseline findings hold even when controlling for likely reverse causality by employing instrumental variable techniques and substituting the accounting-based z-score ratio by market-based indicators of bank risk. Moreover, investigating the relationship between credit risk securitization and single z-score components in order to evaluate significant transmission channels proposed by relevant theoretical literature, we find a negative impact of securitization on bank profitability and capital environment as well as a positive relationship between securitization and the issuing bank's return volatility. Against the background of our empirical results we underline that the decision by the Basel Committee to enhance the new Basel III framework in the field of securitization is a step in the right direction.
Keywords: Credit risk securitization Bank soundness European banking

Cross-border bank lending - Empirical evidence on further determinants from OECD banking markets - Müller, Oliver; Uhde, André (Journal of International Financial Markets, Institutions & Money)
Employing data on foreign bank claims from 13 OECD countries on 51 emerging markets between 1993 and 2007, this study investigates specific characteristics of OECD banking markets and lending banks as new important determinants of cross-border lending. We initially provide empirical evidence that in addition to well-accepted “gravity measures”, characteristics of OECD banking markets as well as lending banks’ attributes may describe further important determinants of cross-border bank lending with regard to our sample. Building subsamples of more-developed emerging markets vs. frontier markets, addressing (non) common lender relationships and analyzing cross border lending flows during different time periods, our analysis additionally reveals that both the determinants’ explanatory power and their direction of impact notably vary with respective subsamples.
Keywords: Foreign bank claims; Gravity measures; OECD banking markets’ characteristics; Lending banks’ characteristics

Measuring the quality of banking supervision revisited - Assessments by German banks before and during the financial crisis - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Governance and Regulation)
This contribution presents and discusses main results of a new survey on the assessment of supervisory quality among German banks in 2010. In particular, it is analyzed if and how supervised banks’ perception of the quality of supervisory authorities and their instruments has changed due to the financial crisis starting in mid-2007. Subsequently, results from the recent survey are compared with findings provided by a former study carried out by the authors in 2006 (Paul, Stein and Uhde, 2008).
Keywords: banking supervision; quality; assessment; banking sector

The Nexus between Monetary Policy, Banking Market Structure and Bank Risk Taking - Michalak, Tobias C.; Uhde, André
Using a sample of stock-listed bank holding companies located in Western Europe over the period from 1997 to 2008 this paper provides empirical evidence that an increase in short-term interest rates as well as an extended period of expansionary monetary policy has a negative impact on European stock-listed banks’ soundness as measured by the Expected Default Frequency. Against this background and in order to evaluate interactions between the risk-taking channel of monetary policy and the competitiveness of a country’s banking market we find a negative impact of an increase in competition in the loan market – proxied by the Boone-indicator – on financial soundness. Referring to the structural-conduct performance (SCP) paradigm, this paper provides further evidence that an increase in concentration in the banking market spurs financial soundness.
Keywords: risk-taking channel; competition; concentration; bank soundness; European banking